TRADISI MEMBAKAR DUPA SEBAGAI MAKNA WANGI-WANGIAN DALAM PERSPEKTIF HADIS - Al Munawarah, Zakiah; Amin, Muhammadiyah; Ahmad, La Ode Ismail (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Burning incense is a long-standing Javanese tradition. When Islam came, it turned out that this tradition was still carried out by some people. Incense, often called frankincense, is an ingredient used in religious ceremonies that emits smoke and gives off a distinctive, fragrant aroma. Offerings and food are given to deceased saints, saints, and ancestors through the smoke of incense. To determine the relationship between perception and preventive behavior in the tradition of burning incense, this research looks at the ritual or tradition of burning incense as a fragrance from a hadith perspective. So this hadith produces the following conclusions: 1) Traditions are passed down from ancestors, can change, and can last for seven generations. Those who still adhere to the mattunu undung tradition still do so today. 2) According to Muslim Hadith Number 4184, Rasulullah SAW enjoyed several smells, including bukhur and others. The hadith reference to mattunu undung is important because undung, also known as bukhur or Frankincense, is used to freshen clothes, linens, and other items. Keywords: Burning incense, Fragrances, Hadith Perspective.